ANALISIS DAN PERANCANGAN SISTEM INFORMASI PEMESANAN JASA MAKE-UP ARTIST (MUA) BERBASIS WEB PADA SITI MARIATUN MAKEUP - Zahara, Fitria Fatimah; Marthiawati, Noneng; Gustinar, Gustinar (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2024)
Nowadays, looking attractive and beautiful has become a daily necessity, especially for the face when attending big events such as graduations, weddings, engagements or other events. A Makeup Artist (MUA) is someone who has a profession as a make-up artist. In Pematang Gajah Jambi there is one make up artist who offers his services, namely Fitriafztmakeup art. However, the ordering process is still done manually, these mua usually offer or promote their services only through social media accounts and by word of mouth. Therefore, a system was developed that can assist the ordering process for customers and provide information on the services provided at Siti Mariatun Makeup. The methods used in this research are observation and interviews. The system development method used is Prototype as the design process. This research produces a system that can order make-up services via the website and can see what services are provided as well as the prices of each make-up service available at Siti Mariatun Makeup to make ordering make-up services easier